Correlating the Anti – Aging Activity with the Bioactive Profile of Chlorella emersonii KJ725233; its Toxicological Studies for a Potential use in Cosmeceuticals - Sawant, Sneha Sunil; Mane, Varsha Kelkar (Pharmacognosy Communications)
Background: Microalgae due to an array of its antioxidant, antimicrobial and anti-inflammatory bioactives have been changing the cosmeceutical market. One such bioactive power pack is Chlorella emersonii KJ725233, a novel, non-fastidious freshwater microalga with an inherently higher anti- oxidant potential. Objective: The present study evaluates its potential use as a cosmeceutical ingredient with arrays of biochemical assays, toxicity studies and GC-HRMS profiling. Materials and Methods: In vitro protein- ase inhibition activity of the methanolic extract of C.emersonii KJ725233 was evaluated using SAAANA, sodium hyaluronate and bovine collagen as substrates respectively. The radical scavenging potential was determined by DPPH assay and was correlated to the total flavonoid content evaluated by aluminium trichloride method. The bioactive composition was evaluated by GC – HRMS analysis. Eye irritation potential and sulforhodamine B assay were carried out using 3T3 fibroblasts cells to ascertain its non-toxic na- ture. Results: The methanolic extract of C.emersonii KJ725233 exhibited a potent elastase inhibition of 92.04±2.27% at a concentration of 1000 µg/mL. This was qualitatively established by the presence of phytol, its isomer and other anti-inflammatory molecules as revealed by GC HRMS profile. Its radical scavenging potential with an IC50 of 5.398±0.138 mg/mL exhibited a correlation coefficient of 0.9977 with its total flavonoid content. Toxicological studies on 3T3 fibroblast cell lines revealed its non – toxic as well as non – eye irritant nature. Conclusion: Its potential anti-aging and antioxidant activity coupled with its non-toxicity thus puts this microalga in the spot light for use in cosmeceutical industry.
Keywords: Chlorella emersonii KJ725233; Anti-aging; Anti-oxidant; Anti- inflammatory; Bioactives; Cosmeceuticals.